2016
DOI: 10.1590/18069061-2015-0052
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Two Strains of Probiotics on the Antioxidant Capacity, Oxidative Stress, and Immune Responses of Salmonella-Challenged Broilers

Abstract: The present study aimed at evaluating the effect of two strains of probiotics (Bacillus subtilis PB6 and Bacillus Cereus var. toyoi) on selected indicators of the antioxidant status and immune responses of broilers before and after challenge with Salmonella enterica subsp. Typhimurium (S. typhimurium). Birds were distributed into the following five treatments: negative control (CTL−); negative control+S. typhimurium (CTL+); antibiotic+S. typhimurium, (AB); Toyocerin®+S. typhimurium (TOYO); and CloSTAT TM + S. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 17 publications
2
15
1
Order By: Relevance
“…On the other hand, results of antioxidant enzymes and MDA in harmony with results of Zhou et al [15] who found significant decrease of antioxidant enzymes in birds infected with necrotic enteritis. On the other hand, Abudabos et al [16] reported that Salmonella typhimurium had no impact on total antioxidant capacity or oxidative stress in challenged broilers. However, agrimos® supplementation significantly decreased serum MDA and increased CAT.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, results of antioxidant enzymes and MDA in harmony with results of Zhou et al [15] who found significant decrease of antioxidant enzymes in birds infected with necrotic enteritis. On the other hand, Abudabos et al [16] reported that Salmonella typhimurium had no impact on total antioxidant capacity or oxidative stress in challenged broilers. However, agrimos® supplementation significantly decreased serum MDA and increased CAT.…”
Section: Discussionmentioning
confidence: 99%
“…infection, but concerns regarding antimicrobial resistance have caused the European Union and many countries to restrict or ban the use of antibiotics (Toghyani, Toghyani, Gheisari, Ghalamkari, & Mohammadrezaei, ). In recent years, several studies have indicated that probiotics, prebiotics, and organic acids can function as antibacterial agents and protect chickens from Salmonella infection (Abudabos, Alyemni, & Zakaria, ; Chen, Tsen, Lin, Yu, & Chen, ; Fernández‐Rubio et al., ; Pourabedin, Chen, Yang, & Zhao, ). It has been suggested that probiotics exert beneficial effects on performance parameters, microbiota composition, and intestinal inflammation, potentially reducing the level of pathogen infection in the intestinal tract (Abudabos, Al‐Batshan, & Murshed, ; Chang, Teng, Lee, & Yu, ; Chen et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The total protein, albumen, triglyceride, Ca, P, aspartate aminotransferase (AST), and alanin aminotransferase (ALT) in plasma were analysed by an automatic analyser (Airone-200RA, Italy) using commercial kits. Total antioxidant (TAS) and total oxidant (TOS) amounts were determined by the ELISA method in plasma (Abudabos et al, 2016). The oxidative stress index was calculated by TOS:TAS ratio.…”
mentioning
confidence: 99%